2004
DOI: 10.1530/eje.0.1500605
|View full text |Cite
|
Sign up to set email alerts
|

The environment and autoimmune thyroid diseases

Abstract: Genetic factors play an important role in the pathogenesis of autoimmune thyroid disease (AITD) and it has been calculated that 80% of the susceptibility to develop Graves' disease is attributable to genes. The concordance rate for AITD among monozygotic twins is, however, well below 1 and environmental factors thus must play an important role. We have attempted to carry out a comprehensive review of all the environmental and hormonal risk factors thought to bring about AITD in genetically predisposed individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
198
1
16

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(216 citation statements)
references
References 207 publications
1
198
1
16
Order By: Relevance
“…The high prevalence of thyroid autoimmunity in women after child-bearing age suggests that pregnancy-related factors could have an influence on the development of AITD. These factors could be hormonal, but it has also been suggested that foetal microchimerism might be important in the pathogenesis of AITD and other autoimmune diseases including scleroderma (6,14,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high prevalence of thyroid autoimmunity in women after child-bearing age suggests that pregnancy-related factors could have an influence on the development of AITD. These factors could be hormonal, but it has also been suggested that foetal microchimerism might be important in the pathogenesis of AITD and other autoimmune diseases including scleroderma (6,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Like other thyroid diseases, AITD is more common in females than in males (4,5). One possible explanation for this female predominance could be the effect of oestrogens on the immune system (6). Another possibility is that foetal microchimerism could contribute to the pathogenesis of AITD (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay D gave non-specific effects (30,31). The action of tobacco on thyroid follicles is quite well known (35)(36)(37)(38). Tobacco use constitutes a risk factor for goiter and its effect is accentuated in the presence of iodine deficiency.…”
Section: Patientmentioning
confidence: 99%
“…38,39 The retrovirus, being able to integrate in the cellular genome, can participate in the development of autoimmune disease, either through the expression of foreign antigens through alteration of expression of autoantigen or through the unbalance of subpopulations of serum lymphocytes. [40][41][42] Some evidences relate HTLV-1 infection as a possible pathogenic factor in the autoimmune thyroid diseases.…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 99%